2022
DOI: 10.1101/2022.12.11.519948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From whole genome to probiotic candidates: a study of potentialLactobacillusstrain selection for vaginitis treatment

Abstract: Vaginitis is a syndrome characterized by not only the invasion of pathogens, but also the lack of Lactobacillus. Lactobacillus supplementation emerged as an innovative therapy for vaginitis which targeted the vaginal microbiota in recent years. However, limited live biotherapeutic products were explicitly marketed for this. The aim of our study is to characterize the potential Lactobacillus candidates for enhancing the treatment of vaginitis. Initially, 98 Lactobacillus isolates with whole genome were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Similarly, Husain et al showed that the colonization rate of the intervention strains and the diversity of the vaginal microbiome did not differ between the probiotic and control groups (49). In fact, L. gasseri TM13 and L. crispatus LG55 used in this study were isolated, cultured, and screened from the human intestine (33). Existing research has shown that there are still many differences in environmental adaptability and systematic developmental characteristics between Lactobacillus strains isolated from the intestine and those isolated from the vagina.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Similarly, Husain et al showed that the colonization rate of the intervention strains and the diversity of the vaginal microbiome did not differ between the probiotic and control groups (49). In fact, L. gasseri TM13 and L. crispatus LG55 used in this study were isolated, cultured, and screened from the human intestine (33). Existing research has shown that there are still many differences in environmental adaptability and systematic developmental characteristics between Lactobacillus strains isolated from the intestine and those isolated from the vagina.…”
Section: Discussionmentioning
confidence: 49%
“…The probiotic strains used in this study are L. gasseri TM13 and L. crispatus LG55 which were isolated from the feces of 2 healthy Chinese people, which we developed in-house. They showed the strong ability to lower vaginal pH, inhibit the growth of pathogenic bacteria and fungi, and alleviated the inflammatory response of BV rats (33). In this study, we aim at evaluating the effectiveness of oral Chinese-origin probiotic strains, L. gasseri TM13 and L. crispatus LG55, with adjuvant MET in treating Chinese BV patients, and investigate the dynamic of the intestine and vaginal microbiome using metagenomic sequencing during the trial.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Husain et al showed that the colonization rate of the intervention strains and the diversity of the vaginal microbiome did not differ between the probiotic and control groups (Husain et al, 2020). In fact, L. gasseri TM13 and L. crispatus LG55 used in this study were isolated, cultured, and screened from the human intestine (Lyu et al, 2022). Further evaluation on whether the differences in the physicochemical environment and differences in patterns of interactions between bacteria in the vagina and the intestine (Human Microbiome Project, 2012) can prevent the transfer of the intervening strains from the intestine to the vagina is needed.…”
Section: Discussionmentioning
confidence: 49%
“…A random number table generated by SPSS 13.0 software was used to randomly assign subjects to the control or probiotic group using a 1:1 ratio. After enrollment, the probiotic group received MET vaginal suppositories (200 mg daily for 7 days) along with oral intake of probiotic solid drinks containing L. gasseri TM13 and L. crispatus LG55 (Lyu et al, 2022) (daily intake ≥ 5×10 9 CFU for 30 days); the control group received the same dose of MET vaginal suppositories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation